2017
DOI: 10.5152/npa.2017.19407
|View full text |Cite
|
Sign up to set email alerts
|

Comparision of Language Features, Autism Spectrum Symptoms in Children Diagnosed with Autism Spectrum Disorder, Developmental Language Delay and Healthy Controls

Abstract: In present study, it is indicated that developmental language trajectories are different in ASD and DLD group. Children, who are diagnosed with ASD, have more receptive language difficulties while children, who are diagnosed with DLD, have more language difficulties in expressive language area. The finding, children who are diagnosed with DLD have more autistic symptoms, shows that autistic symptoms are related with language development, and it is very important to give preference to language education in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…It has been established that language develops commonly by speaking experiences and conditions. Although it depends on cognitive improvement, physiological reliability, and verbal competencies, the environmental demands and support are identified to be vital in the child's learning process [19].…”
Section: Impact Of Asd Characteristics On Learning Abilitymentioning
confidence: 99%
“…It has been established that language develops commonly by speaking experiences and conditions. Although it depends on cognitive improvement, physiological reliability, and verbal competencies, the environmental demands and support are identified to be vital in the child's learning process [19].…”
Section: Impact Of Asd Characteristics On Learning Abilitymentioning
confidence: 99%
“…Individuals with ASD can experience communication deficits in both receptive and expressive language (Özyurt & Eliküçük, 2018 ). Due to the high demand for verbal comprehension inherent in PCIT, studies with PCIT have frequently limited the enrollment to children who have receptive language skills of at least 24 months (Beverly & Zlomke, 2019 ; Owen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have argued that language comprehension (receptive language) is more impaired than language production (expressive language) in autistic children and EL-siblings [e.g., 2,23,24,25], a recent meta-analysis showed that, on average, receptive and expressive language are equally impaired, although individual differences are present [26].…”
Section: Introductionmentioning
confidence: 99%